Priming as a means of preventing skill failure under pressure - Ashford, K. J.; Jackson, R. C. (Journal of Sport & Exercise Psychology, 2010)
The present study examined the effectiveness of a priming paradigm in alleviating skill failure under stress. The priming intervention took the form of a scrambled sentence task. Experiment 1: Thirty-four skilled field-hockey players performed a dribbling task in low- and high-pressure situations under single task, skill-focused, and priming conditions. Results revealed a significant increase in performance time from low to high pressure. In addition, performance in the priming condition was significantly better than in the control and skill-focused conditions. Experiment 2: Thirty skilled field-hockey players completed the same dribbling task as in Experiment 1; however, in addition to the control and skill-focused conditions, participants were allocated to either a positive, neutral, or negative priming condition. Results revealed significant improvements in performance time from the skill focus to the control to the priming condition for the positive and neutral groups. For the negative group, times were significantly slower in the priming condition. Results are discussed in terms of utilizing priming in a sporting context.